Bi0.5Na0.5TiO3-based relaxor ferroelectric ceramic with large energy density and high efficiency under a moderate electric field. Issue 34 (21st August 2019) - Qiao, Xiaoshuang; Wu, Di; Zhang, Fudong; Chen, Bi; Ren, Xiaodan; Liang, Pengfei; Du, Hongliang; Chao, Xiaolian; Yang, Zupei
Abstract : Large energy storage density and high efficiency in Bi0.5 Na0.5 TiO3 -based relaxor ferroelectric ceramic induced by AgNbO3 doping. Abstract : Lead-free relaxor ferroelectric ceramics of (1 − x )(0.6Bi0.5 Na0.5 TiO3 –0.4Sr0.7 Bi0.2 TiO3 )– x AgNbO3 were fabricated by a conventional mixed oxide route. The multifunction of AgNbO3 (AN) doping into the 0.6Bi0.5 Na0.5 TiO3 –0.4Sr0.7 Bi0.2 TiO3 (BNT–SBT) matrix can be divided into two main aspects. First, it enhances the breakdown electric field ( E b ) as a result of reduced grain size and increased resistivity. Second, it improves η via enhancing the relaxation behavior and stabilizing the antiferroelectric (AFE) phase. Eventually, we achieved a large W rec of 3.62 J cm −3 and a high η of 89% simultaneously under a moderate electric field of 246 kV cm −1 as the doping ratio x of AgNbO3 equals 0.05. In addition, the same sample also exhibits excellent temperature stability and good frequency stability, suggesting that AgNbO3 doped BNT–SBT ceramics could be an ideal candidate in high energy storage capacitors.